ANALISIS KEPUASAN KONSUMEN TERHADAP IKAN SEGAR DI PASAR RAWA INDAH KOTA BONTANG - Andi Yusuf; Heru Susilo; Fitriyana (2339-1324, 2016)
The aim of this research was to find out the public perception on the sales as well as to analyze the consumer satisfaction toward the fresh fish marketing at Rawa Indah Market in Bontang Municipality.This research was conducted in 5 months time, starting from the beginning of the year 2015, located at Rawa Indah Market in Bontang Municipality. The sampling method used was purposive sampling. The findings of the research showed that based on needs recognition, the highest number of the respondents revealed that the decision making process of the consumer’s purchase was due to the proximity of the residence to the market. Therefore, the biggest advantage sought by the consumers was the close distance. The highest frequency of information searching was from the sigh board. Moreover, for the alternative evaluation, the highest frequency of respondents revealed that consumers chose to visit Rawa Indah Market because the fish there was fresh. For the consumer’s decision, the highest frequency of respondents showed that their visits were done every afternoon on daily basis. Furthermone, for the marketing result, the highest frequency showed that consumers would keep on buying even though there was a 10 - 40 % price hike. They would come again and their satisfaction level ‘satisfield’. The attributes that should be maintained would be types of fish, accessibility to the location, seller’s responsiveness, friendliness and politiness, safety and convenience, parking areas and market facilities. On the other hand, the attributes which should be improved would be seller’s communication skills, market arrangement and service process. From the CSI calculation, a value of 4.97 % was abtained, which means that consumers visiting Rawa Indah Market in Bontang Municipality was not satisfied enough by the existing attributes. Based on the findings, it could be concluded that the people in Bontang was not too satisfied. Therefore, the related parties or the related government institutionsthat manage Rawa Indah Marketing in Bontang Municipality should improve their quality.